STUDY ON STUDENTS’ SIGNAL LEARNING STRATEGY TO MEMORIZE ENGLISH VOCABULARY - Tawali Tawali (Journal of English Education and Literature, 2026)
This research aimed to analysis Study on Students’ Signal Learning Strategy to Memorize English Vocabulary at Ponpes Haqul Yaqin Sayang-sayang. The subject of this research was first grade VII-A of MTs Haqul Yaqin Sayang-sayang in academic year 2024/2025. The sample of this study were 7 students. The method of this research was qualitative case Study. The technique of data collection applied in this study were interview, recording and documents. Then the procedure of data analysis were data condensation, data display and conclusion drawing and verification used the theory of Miles and Huberman 2014. The result of this research, the researcher found out the types of students strategies in memorizing English vocabulary. The strategies used by the students were making note strategy, repeating strategy, singing strategy and practice strategy. Therefore, the strategies used by students to memorize the meaning and spelling were practice strategy, writing strategy,  memorizing strategy and reading strategy.